The Tramp in American Literature, 1873–1939 (AmeriQuests, 2008)
This essay surveys changing representations of the tramp in American literature from 1873 to 1939. In the late nineteenth century, tramps were understood by middle- and upper-class Americans in terms of deviancy and criminality; but by World War II the tramp had entered the realm of nostalgia. The primary reasons for tramping did not change; what changed was the social meaning assigned to the tramp.